Enhancement of the Mesophilic Anaerobic Co-digestion of Municipal Sewage and Scum - Young, Bradley (Université d'Ottawa / University of Ottawa, 2012)
Scum is an integral component of solids management in MWWTP and is composed of fats, oils, grease and other entrained floatable materials that are collected during primary clarification. Lab scale BMP tests showed the addition of 14.5 g VS/L of scum exhibited the greatest increase in biogas production of 1.6 times per g VS added compared to the control, while a higher additional scum loading of 33.7 g VS/L reduced the biogas yield to 32% of the control reactor. Lab scale semi-continuous digestion measured the effects of scum loading and temperature of pretreatment in the scum concentrator. At 15 d and 20 d HRTs the greatest observed improvement in biogas was achieved by adding 3% scum by volume and pretreating the scum at 70°C in a scum concentrator with respective improvements of 24% and 16%.
Keywords: Scum; FOG; Fats; Oils; Greases; Anaerobic Digestion; BMP; Semi-Continuous; Live/Dead; WWTP